A Portrait of Teaching Writing in Online Classroom - Virga Putra Darma; Kunah Kunah; Siti Lina Nurlina; Salsa Ayu Denistiani (Journal on Education, 2023)
Nowadays, online classrooms are growing in popularity. Especially given the Covid-19 outbreak in Indonesia, which has forced online learning. This study aims to investigate online learning in EFL learners’ writing classrooms. This study uses a qualitative method and a descriptive qualitative research design to examine in detail how teachers teach EFL learners in online writing. Researchers collected data through the technique of nonparticipant observation, and the researcher "observes from the sidelines" the action being observed. The results of this study reveal that the observed teacher's teaching method is not consistent with the four reference strategies employed by the researchers. The four strategies include; building knowledge of field, modeling of text, joint construction of text, and independent construction of text. Because, after being observed, the teacher employs only one strategy to teach writing, specifically building knowledge of field.